Peran Kepala Sekolah Sebagai Supervisor Dalam Meningkatkan Kompetensi Pedagogik Guru Di MD AZZAINIYYAH - Herdi Herdi; Sulaiman Abdul Aziz; Siti Qomariyah (LPPM Politeknik Pratama, 2023)
This study aims to analyze and describe the techniques and efforts of school principals in improving the pedagogic competence of teachers in elementary schools. In this study using a qualitative method, namely research conducted through observation and searching for data directly at the research location. This research is located at MD AZZAINIYYAH. And the research subject or resource person for this research is the principal at MD AZZAINIYYAH. In this study, a result was obtained which stated that the principal's supervision technique was in the form of individual and group techniques. Then the efforts made are conducting training, providing guidance and direction and motivating teachers. Furthermore, after the supervision was carried out, the teacher's performance increased and had an effect on increasing the potential and student learning outcomes at MD AZZAINIYYAH.